2019
DOI: 10.1002/pdi.2238
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and female sexual health: an ongoing challenge

Abstract: Female sexual health remains a much‐neglected area in diabetes clinical medicine; however, it is important for psychological and social well‐being as well as reproductive function. We aimed to explore the views of women regarding the impact of diabetes on sexual health beyond pregnancy and reproduction. We conducted an online survey distributed via social media platforms including Twitter, Facebook and LinkedIn; the survey remained open for four weeks. Questions addressed a range of medical and psychological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…The current study also highlights the limited awareness and knowledge about ED possessed by men with diabetes. It is noteworthy that recruitment to the study was challenging, as compared to recruitment for similar research with women with diabetes that recruited over 250 participants in half the time . This may be a reflection of the ‘taboo’ nature of the subject and the reduced willingness of men to engage or seek help.
Sexual health is an integral part of overall health, well‐being and quality of life Diabetes has been shown to have a significant detrimental effect on sexual healthand well‐being Sexual health problems affect over three‐quarters of people with diabetes The psychosocial impact of sexual health problems results in loss of self‐esteem, loss of feelings of attractiveness, loneliness and negative effects on relationships It is clear that there is still a need for support/resources to be readily available as well as heightened health care professional awareness to help individuals
…”
Section: Discussionmentioning
confidence: 99%
“…The current study also highlights the limited awareness and knowledge about ED possessed by men with diabetes. It is noteworthy that recruitment to the study was challenging, as compared to recruitment for similar research with women with diabetes that recruited over 250 participants in half the time . This may be a reflection of the ‘taboo’ nature of the subject and the reduced willingness of men to engage or seek help.
Sexual health is an integral part of overall health, well‐being and quality of life Diabetes has been shown to have a significant detrimental effect on sexual healthand well‐being Sexual health problems affect over three‐quarters of people with diabetes The psychosocial impact of sexual health problems results in loss of self‐esteem, loss of feelings of attractiveness, loneliness and negative effects on relationships It is clear that there is still a need for support/resources to be readily available as well as heightened health care professional awareness to help individuals
…”
Section: Discussionmentioning
confidence: 99%
“…14 There are three diabetes-related issues that affect sexual function in women. [19][20][21] First, physical problems related to sexual intercourse such as a lack of vaginal lubrication, pain during sex, and a lack of ability to orgasm, can all be a consequence of either high or low blood glucose levels. 22 Second, that people with diabetes are twice as likely to experience depression and this is associated with reduced sexual drive.…”
Section: Novelty Statementmentioning
confidence: 99%
“…Women may not be willing to discuss the problems they experience with a HCP, we know from a cross-sectional questionnaire study (N = 179) that ~70% of women with diabetes had not sought help from a HCP for their sexual dysfunction. 21 Second, women may be unaware that sexual dysfunction might be diabetes related, the same study identified that approximately 50% of women did not know this. 21 Third that some structured education programmes, such as X-PERT Diabetes, Diabetes Education and Self Management for Ongoing and Newly Diagnosed (DESMOND) and Dose Adjustment For Normal Eating (DAFNE), in the United Kingdom do not discuss it, perhaps because this is not recognized as a problem in UK diabetes guidelines.…”
Section: Awareness Identification and Assessment Of Sexual Dysfunction In Women With Diabetesmentioning
confidence: 99%
See 2 more Smart Citations